Haemodynamic Response to a Standard Meal: Consideration on A Case of Significant Blood Pressure Peaks in a Diabetic Hypertensive Patient Treated with ARB and Comparison with Normal Age and Sex Matched Subjects - Ciulla, Michele M; Patrizia, Vivona; Aldini, Giancarlo (Archives of Clinical and Medical Case Reports, 2019)
A standard meal is a stimulus that produces a response that consists in the redistribution of blood flow to the splanchnic district, potentially, affecting systemic blood pressure, this phenomenon was studied in animal models and in critic patient. Here we report a case of a diabetic hypertensive-in-treatment woman where two significant blood pressure peaks were recorded, during lunch and dinner, over an optimal 24/h blood pressure control. In the absence of previous normal reference values in the literature, we retrieved a series of n=10 age and sex matched subjects diagnosed normotensive on the mean of 24/h Ambulatory Blood Pressure Monitoring. We finally present our considerations on the normal response to a standard meal compared to what was found in the literature and in the present case, where an impaired control of resistance is hypothesised, and on the possible mechanisms supporting.